OPTIMIZING THE ROLE OF CORRECTIONAL INSTITUTIONS TO ACHIEVE CRIMINAL OBJECTIVES IN THE PANDEMIC COVID-19 - Saputra, Dandy Rahardiyan (Hukum dan Masyarakat Madani, 2022)
This This writing is entitled 'Optimizing the Role of Institutions in order to Achieve the Goals of Criminalization during the Covid-19 Pandemic'. Today we know that in social life there are many criminal acts around us, therefore criminal law exists as a consequence of criminal liability for people who commit crimes / crimes. The most important sub-function for carrying out criminal law is a correctional institution which has the objective and function of fostering prisoners to achieve the goal of punishment.Reliable sources such as mass media, books, legal experts said that there are still many problems that exist in prisons that tend to have implications for the failure of the functions and objectives of prisons. This problem is even more complicated when the country is facing the Covid-19 pandemic. The existing problems make the correctional institutions not optimal in guiding and guiding prisoners. This condition inspires me to review how to optimize the role of prisons in order to achieve the goals of punishment during the pandemic-Covid 19. The research I am doing is a type of qualitative research with a juridical normative approach.
Keywords: correctional institutions; prisoners; optimization.